Naki-Naki: Oral Tradition of the Karo of North Sumatra - Minawati, Rosta; Alamo, Enrico (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The purpose of this article entitled "Naki-naki: Oral Tradition of the Karo Tribe in North Sumatra" is to examine the context of the traditional courtship system among the young people using oral tradition (oral literature) in the Karo community that developed in ancient times. The Karo community has a unique tradition in finding a life partner. Karo youths, whether male or female, are encouraged to marry (erjabu) as soon as they reach adulthood. Adult males are referred to as "anak perana" and are identified by characteristics such as wearing long pants (saluar gedang) and sleeping in the traditional Karo building called "jambur." Adult females are known as "singuda-nguda" and are identified by characteristics such as menstruation, participation in youth work groups, including communal activities and involvement in artistic festivals (guro-guro-aron).The stages of introduction between young people begin with the tradition of "ngaras-ngaras" and continue with "ertutur." Ertutur can be done with the help of friends, family intermediaries, or directly. The introduction then progresses to a stage known as "Naki-naki." Naki-naki is the moment when the "anak perana" endeavors to convince the "singuda-nguda" to fully accept him for marriage. Naki-naki involves using the eloquent Karo language and is often done at night on the terrace of the house ("ture") or inside the house. The goal is for the couple and their families to get to know each other well.